(untitled) (Research, Society and Development, 2025)
The purpose of this study is to explore the usefulness of mindfulness in the treatment of mood disorders in women, examining its clinical advantages, the available evidence and possible directions for future research and interventions based on integrated mental health practices. A scientometric analysis of articles (2020-2024) was carried out in the Scopus, Web of Science and PubMed databases, with careful selection and analysis of relevant metadata using VOSviewer software. A steady growth in research was identified until 2022, followed by a slowdown in subsequent years. The co-authorship network revealed seven main clusters, with renowned authors, highlighting interdisciplinary and international collaboration, led by countries such as the United States and England. Keyword analysis pointed to central themes such as “emotional regulation”, “cognitive therapy” and “self-compassion”, indicating that these are consolidated and widely studied topics in the field in question. These themes represent the pillars of knowledge or the main focus of current scientific production. We conclude that the field has made significant progress, but still lacks greater representation from developing countries. These results highlight the importance of mindfulness as an evidence-based therapeutic approach and point to the need to expand international collaborations and diversify the contexts of application.